Verification of ignition energy time distribution control for a diluted combustion engine - Eiichiro OHATA; Kazuhiro ORYOJI (Nihon Kikai Gakkai ronbunshu, 2021)
Several high energy ignitions have been proposed to improve ignition performance of diluted combustion recently. One of the major issues in the high energy ignition systems is heat generation of an ignition coil due to increase of power consumption. This study proposes a method to reduce electricity consumption by controlling time distribution of discharge energy while keeping the ignition performance. The following conclusions were obtained as results of verification with an actual engine. (1) A concept for reducing the power supply-demand difference that does not inhibit flame core growth was proposed. (2) To reduce the power supply-demand difference, an ignition coil with an additional active coil was fabricated to enable time distribution control of ignition energy. (3) By controlling the time distribution of ignition energy, both energy saving and ignitability of ignition were achieved, and the prospect of net fuel consumption improvement was obtained.